Characterization of Transport-Enhanced Phase Separation in Porous Media Using a Lattice-Boltzmann Method. (14th May 2019) - Parmigiani, Andrea; Di Palma, Paolo Roberto; Leclaire, Sébastien; Habib, Faraz; Kong, Xiang-Zhao
Abstract : Phase separation of formation fluids in the subsurface introduces hydrodynamic perturbations which are critical for mass and energy transport of geofluids. Here, we present pore-scale lattice-Boltzmann simulations to investigate the hydrodynamical response of a porous system to the emergence of non-wetting droplets under background hydraulic gradients. A wide parameter space of capillary number and fluid saturation is explored to characterize the droplet evolution, the droplet size and shape distribution, and the capillary-clogging patterns. We find that clogging is favored by high capillary stress; nonetheless, clogging occurs at high non-wetting saturation (larger than 0.3), denoting the importance of convective transport on droplet growth and permeability. Moreover, droplets are more sheared at low capillary number; however, solid matrix plays a key role on droplet's volume-to-surface ratio.